Penentuan Hari Baik Dalam Acara Pernikahan Diintegrasikan Dengan Aqidah ASWAJA Nahdliyin - lestari, arum ayu (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
Indonesia is an archipelago country with a diverse culture. One of them is the Javanese tradition of determining the day of marriage. The determination of the day of marriage is a way for the Javanese people to determine the compatibility of the two prospective couples by calculating the value of the birth dates of the two couples before the day of the marriage is determined. Many marriages have failed to be held, which has caused conflict between the two families, only because one party believes in the good day determined by the person considered to be an elder, a wise man, or a shaman. This is certainly contrary to the beliefs of the Aswaja Nahdliyin akidah taught by Imam Hasyim Asyari. The purpose of this study is for readers from both academic and general audiences to know that determining a good day in Islam is not prescribed and can affect a person's faith. This study uses a descriptive method, with data collection techniques using interviews, observations, documentation, literature, and analyzing data using qualitative techniques. The results of the study found that the process of determining a good day to carry out a marriage is not an Islamic teaching, but rather a legacy of the local ancestors. In practice, before the day of the marriage contract is carried out, people who want to get married go to people who are considered to be knowledgeable about this matter to ask for consideration and calculation based on primbon calculation of good days to ask for consideration and calculation based on primbon to determine a good time for the marriage contract. However, according to the view of the Aswaja Nahdliyin akidah, this can damage a person's faith or belief in their creator, because without them realizing it, they have believed in something other than Allah Swt and they also do not believe that misfortune is actually a decree from Allah Swt. Besides that, Allah Swt does not like someone who blames time era because the one who created time era is Allah Swt. keywords: Beliefs, religious Shari'a, Aqidah Aswaja Nahdliyin